Promosi Bisnis Thrifting dalam Meningkatkan Minat Beli Konsumen di Media Sosial Instagram (Bekasansaja) - Amelia, Lola; Puji Isyanto; Neni Sumarni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Amidst the current period of globalization, the fashion industry is undergoing substantial expansion, particularly in Karawang Regency. Bekasansaja, situated in Jalitri Karawang, is a thriving fashion thrift store that has gained popularity among youngsters in the area. Bekasansaja stands out by offering material that captivates consumer attention. The objective of this study is to assess the presentation of tripping advertisements on Instagram, analyze sales promotion strategies for preloved products, identify obstacles in promoting preloved products and propose solutions to overcome them. Additionally, the study aims to investigate the reasons behind selecting the Instagram Feeds and Insta Story features as the primary focus. This research aims to enhance the comprehension of other researchers regarding the promotion of preloved products using Instagram, and to enhance the advancement of promotion techniques for Bekasansaja products.The research methodology employed is qualitative, utilizing a content analysis technique. This involved doing observations, interviews, document analysis, and studying relevant literature.This research focuses on the proprietors and customers of Bekasansaja.The research findings indicate that the @Bekasansaja account utilizes Instagram's Feeds and Insta Story functionalities to promote their sales promotions, employing discounts as a primary strategy. Nevertheless, the primary impediment frequently encountered is a modification in the Instagram algorithm. In order to address this issue, Bekasansaja frequently leverages the personal accounts of their friends who operate shops to enhance the visibility of their brand.